A new Anisian (Middle Triassic) eosauropterygian (Reptilia, Sauropterygia) from Panzhou, Guizhou Province, China. Issue 4 (4th July 2018) - Jiang, Da-Yong; Lin, Wen-Bin; Rieppel, Olivier; Motani, Ryosuke; Sun, Zuo-Yu
Abstract : ABSTRACT—Eosauropterygians rapidly diversified in the Anisian (Middle Triassic), a period by which the invertebrates had already completely recovered from the end-Permian mass extinction. The Pelsonian (Anisian) deposits of the small Panxian and Luoping intraplatform basins in southwestern China alone yielded seven or more eosauropterygian taxa. A new Middle Triassic sauropterygian, Panzhousaurus rotundirostris, gen. et sp. nov., is here described based on an almost complete skeleton from the middle Anisian (Middle Triassic) of Panzhou (Guizhou Province, southwestern China). The upper temporal fenestra smaller than the orbit, the broad and flat parietal table, the cervical ribs with two proximal articular heads, the pachyostotic proximal ends of the dorsal ribs, and the unexpanded sacral ribs indicate that the specimen is a pachypleurosaur-like eosauropterygian. The new species also shows some differences from all other eosauropterygians, such as a rounded and shortened snout, 24 cervical and 20 dorsal vertebrae, a straight ulna with a concave posterior margin, and four distal carpals. Phylogenetic analysis also reveals that Panzhousaurus is an eosauropterygian, closely related to pachypleurosaur-like forms. The discovery of Panzhousaurus enriches our knowledge of the diversity of the Panxian fauna and provides new information to test phylogenetic relationships among known eosauropterygians. http://zoobank.org/urn:lsid:zoobank.org:pub:682A4FDD-C048-469F-867A-9F1D5847BD5A Supplemental Data—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Jiang, D.-Y., W.-B. Lin, O. Rieppel, R. Motani, and Z.-Y. Sun. 2019. A new Anisian (Middle Triassic) eosauropterygian (Reptilia, Sauropterygia) from Panzhou, Guizhou Province, China. Journal of Vertebrate Paleontology. DOI:10.1080/02724634.2018.1480113.